Pengaruh Media Cerita Bergambar terhadap Kemampuan Berbicara Anak Usia 5-6 Tahun di TK Negeri Pembina Merauke - Defi Ambarwati; Hariani Fitrianti; Diah Harmawati; Retno Wuri Sulistyowati (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to determine the effect of pictorial storytelling media on the speaking abilities of children aged 5-6 years at the Pembina Merauke State Kindergarten. This research is quantitative research with the type of research used is an experiment in the form of One Group Pretest-Posttest Design. The research was carried out in group B of the Pembina Merauke State Kindergarten. The research sample was children from the B2 group at the Pembina Merauke State Kindergarten, even semester of the 2022/2023 academic year, totaling 23 children. The data collection techniques used were observation and documentation. Data analysis used paired sample t-test. The research results obtained from the t test, namely the significance value (0.000) was less than 0.05, so that H0 was rejected and Ha was accepted. Thus, it can be concluded that there is pictorial storytelling media on the speaking abilities of children aged 5-6 years at the Pembina Merauke State Kindergarten.